Short-term immunogenicity and safety of hepatitis-A and varicella vaccines in HIV-exposed uninfected and HIV-unexposed South African children. Issue 22 (8th May 2020) - Mutsaerts, Eleonora A.M.L.; Nunes, Marta C.; Bhikha, Sutika; Ikulinda, Benit T.; Jose, Lisa; Koen, Anthonet; Moultrie, Andrew; Grobbee, Diederick E.; Klipstein-Grobusch, Kerstin; Weinberg, Adriana; Madhi, Shabir A.
Highlights: No effect of HIV exposure on immunogenicity of hepatitis-A and varicella vaccines. Most children were seropositive after single dose hepatitis-A vaccine. Less than half seroconverted after one dose of varicella vaccine. Abstract: Background: HIV-exposed uninfected (HEU) children have increased risk of infectious morbidity during early childhood. We evaluated the short-term immunogenicity and safety of single dose inactivated hepatitis-A virus (HAV) vaccine and live attenuated varicella zoster virus (VZV) vaccine in South African children. Methods: 195 HIV-unexposed and 64 HEU children received either one dose of HAV or VZV vaccine at 18 months of age. Blood samples were tested for hepatitis-A or VZV antibodies before and one month after vaccination by chemiluminescent microparticle immunoassay and enzyme-linked immunosorbent assay, respectively. All children were evaluated for solicited adverse events (AEs). Results: One-month post-vaccination, a similar percentage of HIV-unexposed (91.8%) and HEU (82.9%) children were seropositive for hepatitis-A (p = 0.144). VZV antibody geometric mean fold-rise was also similar in HIV-unexposed (5.6; 95%CI: 4.6–6.7) and HEU children (5.1; 95%CI: 3.7–7.2); however, only 44% HIV-unexposed and HEU seroconverted (titers > 50 mIU/ml). AEs occurred with similar frequency and severity between groups, except for more systemic AEs after VZV vaccination in HEU than HIV-unexposed children. Conclusions: Single dose HAV and VZV vaccine was similarly immunogenic in HIV-unexposed and HEU children. We did not identify differences in short-term humoral immunity after administration of either a live attenuated or inactivated vaccine. Seroconversion rates after a single dose of VZV vaccine were, however, lower compared to reports from previous studies (85–89%). Clinical trials registration: NCT03330171.